The Effectiveness of Health Education on Increasing Patient Knowledge About Hypertension in Kutalimbaru Village, Deli Serdang Regency - Sartini Bangun; Elny Lorensi Silalahi (Newinera Publisher, 2022)
Hypertension has consistently been a major cause of morbidity and death in various countries and its prevalence continues to increase. This study aims to determine the effectiveness of health education in increasing the knowledge of hypertensive mothers about hypertension in Kutalimbaru Village, Deli Serdang Regency. The research design is a Quasi-experiment with a pre-and post-test design.70 Systematic random sampling of hypertensive mothers where the treatment group (n = 35) and the control group (n = 35). The research data is the level of knowledge about hypertensive mothers. Statistical analysis was analysed The SPSS software independent t-test The results showed that after counselling there was an increase in the knowledge of hypertensive mothers about hypertension (p-value= 0.001). Health education is effective in increasing family knowledge about hypertension.